FORMATION OF ENVIRONMENTAL CONSCIOUSNESS OF THE FUTURE OF TEACHERS OF BIOLOGY IN THE PROCESS OF PEDAGOGICAL PRACTICE - Yu.O. Saunova (Academy of Cognitive and Natural Sciences, 2009)
This article considers peculiarities of pedagogical practice organization of future Biology's teachers, establishes its significance in ecological conscious forming. The author pays attention to pedagogical practice organization and its content's pecularities.